2006
DOI: 10.1177/1420326x06062582
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Humidity on the Survival of MRSA on Hard Surfaces

Abstract: Methicillin resistant Staphylococcus aureus(MRSA) is an ongoing clinical problem world-wide and a recognised cause of nosocomial infection. In the UK it has been reported that approximately 100,000 patients acquire nosocomial infections per annum, of which 6000 die [1]. If MRSA survives for long periods in health-care environments, this may contribute to infection transmission from fomites. We evaluated the effect of humidity on the survival of MRSA on five different hard surfaces commonly found in health-car… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 10 publications
0
19
0
Order By: Relevance
“…It is likely that deposited LA-MRSA can survive for longer periods on soil surfaces. While there is no exact information about the survival time of MRSA on soil, it is known from laboratory experiments that human MRSA strains show high tenacity and can survive on hard surfaces for weeks (17). Therefore, we assume that deposited MRSA is able to accumulate on soil surfaces around the barns, provided that it is not washed away by rainfall.…”
Section: Discussionmentioning
confidence: 99%
“…It is likely that deposited LA-MRSA can survive for longer periods on soil surfaces. While there is no exact information about the survival time of MRSA on soil, it is known from laboratory experiments that human MRSA strains show high tenacity and can survive on hard surfaces for weeks (17). Therefore, we assume that deposited MRSA is able to accumulate on soil surfaces around the barns, provided that it is not washed away by rainfall.…”
Section: Discussionmentioning
confidence: 99%
“…De Luca et al [34] and Makison and Swan [42] reported the presence of coagulase negative staphylococci in different environments (in atmospheric air and on hard hospital surfaces) with low humidity. These bacteria may occur as agglomerations of cells, or may be rafted into the air on plant or animal fragments, on soil particles [40].…”
Section: Seasonal Variationmentioning
confidence: 98%
“…A strong correlation has been found between the transmission of viruses and absolute humidity, and viruses outbreak when the vapor content of the air decrease . Several controlled studies concluded that both RH and humidity ratio values influence the survival of viruses and bacteria …”
Section: Indoor Environmental Parameters Impacting Patient Outcomesmentioning
confidence: 99%